Transparency by Conformity: A Field Experiment Evaluating Openness in Local Governments - ben-Aaron, James; Denny, Matthew; Desmarais, Bruce; Wallach, Hanna (Public Administration Review, 2017)
Sunshine laws establishing government transparency are ubiquitous in the United States; however, the intended degree of openness is often unclear or unrealized. Although researchers have identified characteristics of government organizations or officials that affect the fulfillment of public records requests, they have not considered the influence that government organizations have on one another. This picture of independently acting organizations does not accord with the literature on diffusion in public policy and administration. This article presents a field experiment testing whether a county government’s fulfillment of a public records request is influenced by the knowledge that its peers have already complied. The authors propose that knowledge of peer compliance should induce competitive pressures to comply and resolve legal ambiguity in favor of compliance. Findings indicate peer conformity affects both in the time to initial response and in the rate of complete request fulfillment.